1981
DOI: 10.1161/01.cir.63.3.489
|View full text |Cite
|
Sign up to set email alerts
|

Non surgical coronary artery recanalization in acute transmural myocardial infarction.

Abstract: SUMMARY In 41 consecutive patients with an acute transmural myocardial infarction (AMI) admitted within 3 hours after the onset of symptoms, we tried to recanalize the occluded coronary artery by an intracoronary infusion of streptokinase (SK) (2000 units/min). SK infusion was preceded by (1) an intracoronary injection of 0.5 mg nitroglycerin to rule out coronary artery spasm, (2) an attempt to recanalize the vessel mechanically with a flexible guidewire, and (3) an intracoronary injection of plasminogen (500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
4

Year Published

1982
1982
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 454 publications
(64 citation statements)
references
References 17 publications
3
57
0
4
Order By: Relevance
“…Even among clinical studies, varied incidence of reperfusion arrhythmias has been demonstrated. 2,[27][28][29][30][31] These results suggest that mechanisms responsible for AIVR and VT in clinical cases might be somewhat different from those observed in experimental models. In the present study, we clinically demonstrated for the first time that AIVR and VT that occur after reperfusion are probably cAMP-mediated arrhythmias and are therefore likely to be triggered arrhythmias.…”
Section: Electrophysiological Mechanisms Of Reperfusion Arrhythmiasmentioning
confidence: 82%
“…Even among clinical studies, varied incidence of reperfusion arrhythmias has been demonstrated. 2,[27][28][29][30][31] These results suggest that mechanisms responsible for AIVR and VT in clinical cases might be somewhat different from those observed in experimental models. In the present study, we clinically demonstrated for the first time that AIVR and VT that occur after reperfusion are probably cAMP-mediated arrhythmias and are therefore likely to be triggered arrhythmias.…”
Section: Electrophysiological Mechanisms Of Reperfusion Arrhythmiasmentioning
confidence: 82%
“…Fur thermore, there have been many previous experimental reports of serious arrhythmias induced by the rapid re lease of coronary occlusion (18)(19)(20). In clinical studies, Goldberg et al (21) reported that reperfusion arrhyth mias occurred in 82010 of patients during restoration of anterograde coronary flow, and Mathey et al (22) reported that 5 of 41 patients showed ventricular fibrilla tion during thrombolytic reperfusion. In reperfusion ar rhythmias, there may be increased heterogeneity of electri cal activity in necrotic versus viable cells, leading to the instability of the cell membrane balance (20); the etiology of reperfusion arrhythmias appears to be different from that of arrhythmias produced during coronary occlusion (18).…”
Section: Discussionmentioning
confidence: 99%
“…Patients who met all the following criteria were included in this study: (1) age 70 years or less, (2) clinical presentation suggestive of evolving acute myocardial infarction, (3) electrocardiogram showing ST segment elevation of ¢ 1.5 mm in two or more leads or marked T wave changes alone in an otherwise classic clinical presentation, (4) no contraindication to thrombolytic therapy or anticoagulation, (5) emergency catheterization and thrombolytic therapy available within 12 hr of onset of pain (as an exception, patients with evolving acute infarction and recurrent severe pain 12 to 24 hr after infarction were eligible, and (6) consent given for emergency coronary and left ventriculography and reperfusion intervention.…”
Section: Methodsmentioning
confidence: 99%